ANALISIS DESAIN INTERIOR DAN EKSTERIOR DALAM MENGEMBANGKANN KECERDASAN NATURALIS PADA ANAK KELOMPOK B 1 DI RA AS-SYAFIQAH KOTARIH BARU KABUPATEN SERDANG BEDAGAI - Nurmaya Ningsih; Hasnah Siahaan; Mardiah Mardiah; Cut Rafyqa Fadhilah (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Naturalist intelligence is an intelligence that is a combination of the characteristics of a child which includes skills in recognizing, classifying flora and fauna and other natural objects and having awareness of environmental conditions and the beauty within themselves. The environment and nature are the most important thoughts for the early development of a child's mindset. Through the intermediaries of the environment and nature, children are free to move and develop their naturalist intelligence. Writing this thesis aims to find the relationship between interior and exterior design in developing children's naturalist intelligence. The research method used is qualitative research where this research has nothing to do with numbers but this research will explain in sentences or in the form of a description of the phenomenon that is happening when researched.